Excellence in education policies: Catering to the needs of gifted and talented or those of self-interest?. (November 2018) - Rasmussen, Annette; Lingard, Bob
Globally, education policy reforms are increasingly aimed at attending to excellence in education. This is mainly expressed as attempts at raising educational standards generally, but also of identifying intellectual elites and making special provisions for them. Denmark, which is otherwise considered an exponent of an equality-oriented tradition in education, is now pursuing strategies of developing talent throughout the educational system, which is to cater more to the needs of so-called gifted and talented students. This policy is claimed to have found inspiration from Australia, where some of the states have been pursuing such policies for several years and where we find a more developed tradition for this. The paper is focused on understanding what concept of excellence such education policies imply; we aim to analyse the targeted groups with respect to means of identification and development, and to analyse the wider implications of such policies. The analysis is empirically focused on education policy documents on gifted and talented educational provisions at national/state level. Beginning with the political discourse of talent development in education as it has appeared in Denmark, we analyse this in relation to the policies and curricular provisions for the gifted and talented in England and Australia.